Leaf Litter Decomposition and Nutrient Release of Three Native Tree Species in a Drained Tropical Peatland in Riau, Indonesia - Ahmad Junaedi; Nina Mindawati; Avry Pribadi; Suryo Hardiwinoto (HAYATI Journal of Biosciences, 2022)
The decomposition and its nutrient release were the key ecological process that had a broad role in the forest ecosystem. This study aimed to investigate the leaf litter decomposition rate and its nutrient release of three native tree species of tropical peat swamp forest, namely Macaranga pruinosa, Macaranga gigantea, and Cratoxylum arborescens and one exotic species i.e Acacia crassicarpa. The decomposition and nutrient release were monitored in an experimental plot using litter bag technique. The initial litter quality of each litter and micro-environment properties were also observed. The result showed that the decomposition and its nutrient release were insignificantly different among native tree species and also between native species and Acacia crasssicarpa. The litter decomposition of all tree species was slow; with the range of k was 0.98-1.19 year-1. However, the P and K release from the decomposition of native species litter after four months of incubation were quickly, ranging 70-74% and 88-93%. We were suggested that the high of lignin content in the leaf litter (36-39%) was the main factor that made slow decomposition. These findings could be used as one of the tools in tree species selection for peat swamp forest rehabilitation.